A discussion about beauty, eroticism and the significance of muscle in Simone de Beauvoir’s the second sex and Yukio Mishima’s forbidden colours and confessions of a mask - Teo, Gerald Emmanuel (2015)
In the following essay, I examine the work, The Second Sex by Simone de Beauvoir alongside the novels, Forbidden Colours and Confessions of a Mask by Yukio Mishima. The former is a work of classical feminism that was written in 1949 and that addresses the question of why women all over the world in the 1940s occupied an inferior position to men whereas the latter are both gay-themed novels that were written in 1951 and 1949, respectively and that tell respectively, the story of an ugly, old novelist named Shunsuke Hinoki who uses a young and beautiful homosexual named Yuichi Minami to exact revenge on several of his former love interests and the story of a self-identified invert named Kochan who struggles to reconcile the demands placed upon him by his sexuality with the demands placed upon him by his society.